2014
DOI: 10.1007/s11274-014-1648-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of zinc resistance in a plant growth promoting Pseudomonas fluorescens strain

Abstract: Bacterial systems have evolved a number of mechanisms, both active and passive, to manage toxic concentrations of heavy metals in their environment. The present study is aimed at describing the zinc resistance mechanism in a rhizospheric isolate, Pseudomonas fluorescens strain Psd. The strain was able to sustain an external Zn(2+) concentration of up to 5 mM in the medium. The strategy for metal management by the strain was found to be extracellular biosorption with a possible role of exopolysaccharides in met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…We have also characterized zinc biosorption by this strain (Upadhyay and Srivastava 2014) In the present communication, we demonstrate the zinc biofertilization potential of this strain and its impact on the growth and development of wheat crop.…”
Section: Introductionmentioning
confidence: 57%
“…We have also characterized zinc biosorption by this strain (Upadhyay and Srivastava 2014) In the present communication, we demonstrate the zinc biofertilization potential of this strain and its impact on the growth and development of wheat crop.…”
Section: Introductionmentioning
confidence: 57%
“…The shake cultures were raised on Controlled Environment Shaker Incubator (Kühner, Switzerland) at 200 rpm at 30°C for the required period of time. Growth was determined turbidometrically at 600 nm, as per the protocol described earlier (Upadhyay and Srivastava, 2014 ). All chemicals used in the study were of analytical grade and purchased from Sigma Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent Pseudomonas strain Psd is a rhizosphere isolate, possessing multiple PGP properties and biocontrol potential (Upadhyay and Srivastava, 2008 , 2010 ; Kochar et al, 2011 ). Besides, we have earlier demonstrated that this strain possesses high resistance toward Zn 2+ , which emanates from extracellular biosorption (Upadhyay and Srivastava, 2014 ). We have also established that Zn 2+ biosorption is coupled with an increase in the total EPS production.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Plant growth promoting rhizobacteria (PGPR) have been known for long time to be involved in plant growth promotion via mechanisms such as phytohormone production, suppression of plant diseases and improved nutrient acquisition by nitrogen fixation, phosphate solubilization and metal accumulation (Martínez Viveros et al 2010, Upadhyay andSrivastava 2014). Apart from this, PGPR are also known to be key players in bioremediation of contaminated soils due to their ability to accumulate metals (Zhuang et al 2007).…”
Section: Introductionmentioning
confidence: 99%